Studi Fenomenologi: Budaya Manajemen Diet Bagi Lanjut Usia Dengan Diabetes Melitus - Lilyana, Maria Theresia Arie; Pae, Kristina (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2022)
DM patients must be obedient in carrying out treatment therapy management to avoid complications of acute and chronic DM disease such as: stroke, heart disease, nephropathy and retinopathy. Therapeutic management that must be carried out by DM patients includes medical nutrition therapy, physical activity, education, and pharmacological therapy. This study aims to explore the experience of the elderly in implementing the DM diet. Methods: This qualitative study explores the experiences of 4 respondents in running the DM diet. Results: The themes of this study include: sources of information on DM diet, DM diet that is understood, implementation of DM diet being followed. Discussion: sources of information on dieting are doctors and nutritionists, the DM diet is understood to reduce blood sugar levels so that the implementation of the diet is done by reducing the consumption of rice and fat in their daily menu. Conclusion: The main source of information in DM therapy management is from doctors and nutritionists with the aim of controlling blood sugar levels by reducing the intake of carbohydrates and sweet foods such as cakes. Suggestion: there is an educational model that is easy to understand and implement in the daily life of the elderly with DM.